The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1182/blood-2016-09-742825
|View full text |Cite|
|
Sign up to set email alerts
|

Plasmin and plasminogen induce macrophage reprogramming and regulate key steps of inflammation resolution via annexin A1

Abstract: Key Points Plg and Pla induce macrophage reprogramming and promote resolution of acute inflammation. Plg and Pla enhance the efferocytic capacity of macrophages and override the prosurvival effect of LPS on neutrophils via annexin A1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
128
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 70 publications
(150 reference statements)
11
128
1
Order By: Relevance
“…Next, we validated the efferocytosis data using a different protocol in which apoptotic neutrophils are injected as prey into the peritoneal cavity of mice after the mice are injected with the drug, and we found that L‐cycloserine, FTY720, JTE013, or DTD increased the efferocytic ability of peritoneal macrophages (Fig. ).…”
Section: Resultsmentioning
confidence: 85%
“…Next, we validated the efferocytosis data using a different protocol in which apoptotic neutrophils are injected as prey into the peritoneal cavity of mice after the mice are injected with the drug, and we found that L‐cycloserine, FTY720, JTE013, or DTD increased the efferocytic ability of peritoneal macrophages (Fig. ).…”
Section: Resultsmentioning
confidence: 85%
“…Others have shown that plasmin activates NF‐κB and induces expression of proinflammatory cytokines in monocytes and macrophages . Plasmin also may contribute to the resolution of inflammation . The protease activity of plasmin appears essential for its effects on cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…The protease activity of plasmin appears essential for its effects on cytokine expression. Plasminogen receptors, such as annexin A2/S100A10 complex, annexin A1, α‐enolase, and plasminogen‐R TK , play a critical role in mediating the effects of plasmin in inflammation . One function of plasminogen receptors may be to facilitate plasminogen activation and then deliver plasmin to cell‐signaling receptors in the protease‐activated receptor (PAR) family .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the mouse have demonstrated that the Plg/plasmin system influences macrophages by transcriptional modulation of several genes to increase their efferocytosis activity and by promoting their reprogramming from the proinflammatory (M1) to the resolution (M2) type . However, these studies have not identified the Plg receptor on the phagocytes.…”
Section: Discussionmentioning
confidence: 99%